Plumbing : design and estimate - Fajardo, Max B. ([Place of publications not identified] 5138 Trading, 2001)
Plumbing is defines as the art and science of installing pipes, fixtures and other apparatus to convey and supply water in buildings and to dispose and discharge waste water and other liquids, gases and other substance out of building .
Chapter1. Plumbing -- Chapter2. Plumbing Materials -- Chapter3. Measuring, cutting and Joining Pipes -- Chapter4. Sewage Disposal Systems -- Chapter5. The Waste Pipe -- Chapter6. The Soil Pipe -- Chapter7. The House Drain -- Chapter8. The House Sewer -- Chapter9. The Storm Drain -- Chapter10. Traps for Plumbing Fixtures -- Chapter11. Plumbing Ventilations -- Chapter12. The Sovent System -- Chapter13. Cold Water Supply in Building -- Chapter14. Hot Water Supply in Building -- Chapter15. Plumbing Fixtures -- Chapter16. Fire Protection in Building -- Chapter17. Plumbing Installation and Materials .
Keywords: PLUMBING -- MEASUREMENTS; PLUMBING -- DESIGNS; PLUMBING -- MATERIALS